Humanizing brands through story-telling in magazine advertising - Martín de la Rosa, Victoria; Domínguez Romero, Elena (Círculo de Lingüística Aplicada a la Comunicación, 2016)
Within the framework of Conceptual Metaphor Theory, where metaphor allows human beings to map structure from concrete realms of experience (based on sensory-motor experience) to other more abstract domains, the Source-Path-Goal schema stands as one of the central concepts in human conceptualization. Its importance lies in the way it unifies and gives structure to concepts of motion. In turn, this embodied notion shapes our understanding of a purposeful activity, in which some path is traversed in order to reach for a goal, and our understanding of story-telling where, based on the same notion of a path, there is a development of characters in quest of a goal. On this basis, our purpose in this paper is to analyze three magazine advertisements in an attempt to reveal Conceptual Metaphor Theory, embodied cognition, image schemas, magazine advertising